Fumarase From Cyanidioschyzon merolae Stably Shows High Catalytic Activity for Fumarate Hydration Under High Temperature Conditions - Ito, Shoki; Iwazumi, Kaori; Sukigara, Haruna; Osanai, Takashi (Frontiers in Microbiology, 2020)
Fumarases (Fums) catalyze the reversible reaction converting fumarate to L-malate. There are two kinds of Fums: Class І and ІІ. Thermostable Class ІІ Fums, from mesophilic microorganisms, are utilized for industrial L-malate production. However, the low thermostability of these Fums is a limitation in industrial L-malate production. Therefore, an alternative Class ІІ Fum that shows high activity and thermostability is required to overcome this drawback. Thermophilic microalgae and cyanobacteria can use carbon dioxide as a carbon source and are easy to cultivate. Among them, Cyanidioschyzon merolae and Thermosynechococcus elongatus are model organisms to study cell biology and structural biology, respectively. We biochemically analyzed Class ІІ Fums from C. merolae (CmFUM) and T. elongatus (TeFum) and evaluated their industrial applicability.CmFUM and TeFum showed the highest activity at 52 and 45-55 °C, respectively. Both CmFUM and TeFum preferentially catalyzed fumarate hydration. CmFUM had higher catalytic activity during fumarate hydration compared to that of Class ІІ Fums from other organisms and TeFum. Thermostability tests of CmFUM revealed that CmFUM showed higher thermostability than that of Class ІІ Fums from other microorganisms. In summary, CmFum showed high activity and thermostability and therefore, is suitable for industrial L-malate production.